Management at Science-Intensive Industry: Key Lines in Development and Technology of Choosing Solutions - S. B. Baurina; O. A. Elina (Вестник Российского экономического университета имени Г. В. Плеханова)
In today’s conditions of dynamic and highly competitive business-environment elaboration of efficient strategy of enterprise development requires innovative approaches and technologies that can provide necessary flexibility, adaptability and timely strategic decision-making. Traditional methods of strategic planning based on extrapolation of past trends and reactive response on environment changes cannot meet challenges of the present time. Fast development of information technologies, market globalization, competition toughening, decrease in life cycle of products and technologies and growing role of non-tangible assets and intellectual capital require from highlytechnological companies continuous search for new sources of competitive advantages and fast adaptation of their strategies to changing conditions of business-landscape. The degree of scientific elaboration of the problem of strategic development of highly-technological enterprises is characterized by availability of a serious volume of research dealing with various aspects of the present subject. However, in spite of considerable attention of researchers to problems of strategic development at highly-technological enterprises, a lot of theoretical and applied issues in the sphere are still underdeveloped. The goal of the article is to identify key lines in the development of today’s science-intensive business and systematize technologies for choosing solutions for highly-technological works. The authors provided detailed characteristics of current technologies of strategy elaboration; in particular they described scenario planning, dynamic capacities, business-ecosystems, platform, strategies, ‘blue ocean’ strategies and agile-strategies. The article gave examples of realizing the mentioned variants of technologies of solution choosing in well-known foreign and Russian companies. Specific features of shaping and realizing strategies of developing highly-technological business in conditions of sanction restrictions were shown. Successful practices of strategic development of highly-technological works were analyzed and opportunities were demonstrated to transform this experience into activities of science-intensive companies on the territory of the Russian Federation. Academic conclusions and findings of the research could be useful both for management of Russian companies to reach competitive advantage on market and representatives of other professional communities interested in getting tools of strategic management. Research methods included comparative and systemic analysis, qualitative and quantitative approaches.